The practice of medicinal chemistry - Wermuth, Camille Georges;Aldous, David;Raboisson, Pierre;Rognan, Didier (Amsterdam : Elsevier Science, 2015)
The Practice of Medicinal Chemistry, 2E, is a single-volume source on the practical aspects of medicinal chemistry. The successful first edition was nicknamed "The Bible" by medicinal chemists, and the second edition has been updated, expanded and refocused to reflect developments over the last decade. Emphasis is put on how medicinal chemists conduct their search for and design of new drug entities. In contrast to competing books, it focuses on the chemistry rather than pharmacological concepts or descriptions of the various therapeutic classes of drugs. Most medicinal chemists working in the pharmaceutical industry are organic synthetic chemists who must acquire a strong knowledge of medicinal chemistry as they enter the industry. This book aims to be their practical handbook - a complete guide to the drug discovery process.
General aspects of medicinal chemistry -- Lead compound discovery strategies -- Primary exploration of structure-activity relationships -- Substituents and functions: qualitative aspects of structure-activity relationships -- Spatial organization, recepor mapping and molecular modeling -- Chemical modifications influencing the pharmacokinetic properties -- Pharmaceutical and chemical means to solubility and formulation problems
Includes index.
Keywords: PHARMACEUTICAL CHEMISTRY